Gaya Kepengarangan Perempuan dalam Novel Indonesia dari Perspektif Stilistika - Sovia Wulandari; Liza Septa Wilyanti; Anggi Triandana (Universitas Batanghari Jambi, 2022)
This study aims to examine and classify women's writing styles in Indonesian novels from a stylistic perspective. The contribution of the results of this study is to provide a description of the authorship style of women in the novel. The method used in this study is a descriptive qualitative method with a stylistic study approach. Data analysis using content analysis. The research data are related to linguistic aspects which include diction, grammatical arrangement, and figurative language. The result of this research is that there are eight styles of female authorship in Indonesian novels. The style of authorship based on the aspect of the use of diction is classified into vulgar, regional, scientific, and popular styles. Meanwhile, the style of writing based on grammatical structure is repetition style. Furthermore, the style of writing based on figurative language is classified into satire, hyper, and fantasy styles. The eight styles of authorship show the characteristics of Indonesian women's writing styles in fiction in the form of novels.